2016
DOI: 10.1002/hep.28898
|View full text |Cite
|
Sign up to set email alerts
|

Rifaximin has no effect on hemodynamics in decompensated cirrhosis: A randomized, double‐blind, placebo‐controlled trial

Abstract: Four weeks of treatment with rifaximin did not reduce the hepatic venous pressure gradient or improve systemic hemodynamics in patients with cirrhosis and ascites; rifaximin did not affect glomerular filtration rate or levels of vasoactive hormones. (Hepatology 2017;65:592-603).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 41 publications
3
60
0
2
Order By: Relevance
“…However, our negative efforts to demonstrate such an effect is in line with our previous data from this randomized trial, where we found no effect of rifaximin-α on clinical parameters such as HVPG and cardiac output, no effect on biochemical parameters and inflammation markers (e.g. Tumor necrosis factor alpha and Interleukins 6, 10 and 18), and no effect on the composition of bacterial DNA in blood or stool [23, 24]. …”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…However, our negative efforts to demonstrate such an effect is in line with our previous data from this randomized trial, where we found no effect of rifaximin-α on clinical parameters such as HVPG and cardiac output, no effect on biochemical parameters and inflammation markers (e.g. Tumor necrosis factor alpha and Interleukins 6, 10 and 18), and no effect on the composition of bacterial DNA in blood or stool [23, 24]. …”
Section: Discussionsupporting
confidence: 89%
“…Baseline characteristics and demography in the two groups are shown in Table 1 and reported previously [23, 24]. Trial flow chart is reported previously and in Fig 1 [24].…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…However, the findings remain unconvincing to date. In some studies, rifaximin showed a major preventive effect [62,63], while in others, this effect could not be determined or was only minor [64,65]. Thus, while there is some evidence that some patients might benefit from rifaximin, a better selection and stratification of patients is required in the clinical setting.…”
Section: Poorly Absorbable Antibiotics As Gut-liver Axis Interventionmentioning
confidence: 99%